Một số phương pháp điều khiển truy nhập trong hệ thống bảo vệ thông tin cơ sở dữ liệu - Hạnh, Đào Thị Hồng (Journal of Computer Science and Cybernetics, 2016)
This paper presents a new user authentication scheme, which does not require a management file for user’s password. It has a high security, realizing the authentication of a large number of uses by a single public key. This paper presents a access matrix control by a real number C between 0 and 1. Finally, the paper proposes an access control scheme in distributed database with a single key, which has security of public key Merkle-Knapsack.